Food Safety Assessment of Wet Noodles: Detection of Methanyl Yellow in Kebon Roek Traditional Market, Mataram City - Dini Yuliansari; Nurhidayatullah Nurhidayatullah; Renaldi Renaldi (Jurnal Pijar MIPA, 2026)
Wet noodles are one of the most commonly consumed food products in Indonesia and are often used as an alternative staple food to rice. To enhance product appearance, some producers may add coloring agents to wet noodles. One of the prohibited synthetic dyes is Metanil Yellow, which can cause various health problems, including respiratory irritation, skin irritation, eye irritation, and an increased risk of cancer when consumed continuously over a long period. This study aimed to determine the presence of Metanil Yellow in wet noodles sold at Kebon Roek Market in Ampenan, Mataram City, in 2025. This study employed a descriptive qualitative research design. Samples were selected using purposive sampling based on the physical characteristics of wet noodles suspected to contain Metanil Yellow. A total of five wet noodle samples were analyzed qualitatively using the wool yarn method at the Environmental Health Laboratory of the Mataram School of Environmental Engineering (STTL Mataram). A positive result for Metanil Yellow was indicated by a purple-reddish color change in the wool yarn after the addition of 37% hydrochloric acid (HCl). The results showed that none of the tested samples exhibited a color change in the wool yarn after testing, indicating that all samples were negative for Metanil Yellow. These findings suggest that the wet noodles sold at Kebon Roek Market, Ampenan, Mataram City, during the study period complied with food safety standards prohibiting synthetic dyes in food products.